Escherichia coli Modulator of Drug Activity B (MdaB) Has Different Enzymological Properties to Eukaryote Quinone Oxidoreductases. Issue 8 (10th July 2019) - Megarity, Clare F.; Timson, David J.
Abstract: Some quinone oxidoreductases exhibit negative cooperativity towards inhibitors. In human NQO1, this is mediated by flexibility around glycine‐150. Here we investigated the eubacterial orthologue, Modulator of Drug Activity B (MdaB) to determine if it shows cooperativity towards substrates or inhibitors and to investigate molecular recognition of the inhibitor, dicoumarol. Like human NQO1, MdaB did not show cooperativity towards substrates. However, unlike NQO1, it was only weakly inhibited by dicoumarol. Alanine‐127 in MdaB is the structurally equivalent residue to Gly‐150 in human NQO1. With the intention of increasing protein flexibility in MdaB, this alanine was altered to glycine. This change did not increase cooperativity towards inhibitors or NADPH. Based on structural alignment to NQO1 in complex with dicoumarol, an asparagine in the active site was changed to alanine to reduce steric hindrance. This change resulted in enhanced inhibition by dicoumarol, but the inhibition was not cooperative. Both changes were then introduced simultaneously. However, the additional increase in flexibility afforded by the change to glycine did not enable negative cooperativity towards dicoumarol. These results have implications for the evolution of quinone oxidoreductases and their potential use as biocatalysts. Abstract :